1996
DOI: 10.1039/cc9960000537
|View full text |Cite
|
Sign up to set email alerts
|

A stereoselective route to medium-ring cis-1,n-dialkyl-1,n-diphosphacycloalkanes

Abstract: Quaternisation of 1, ( k + 2)-diphosphabicyclo[k.l.0]alkanes 2, followed by treatment of the monoquaternary salts with alkyllithium or Grignard reagents produces the &isomers of 1,n-disubstituted-1,n-diphosphacycloalkanes 3 exclusively; examples containing eight-, nine-and ten-membered rings are described and the structures of two of these compounds 3a and 3f have been determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…Phosphatrane molecules are a tricyclic cage‐like heterocycles which present the possibility to have a transannular dative bond with a nitrogen or another heteroatom. The pioneer synthetic work in the groups of Alder and Verkade showed that depending of the size, substituents and environment they can adopt out:out and/or in:out conformations. In previous works, we have demonstrated that the change of the conformation can have profound implications in the nucleophilic character of the terminal phosphorous atom, and thus, the equilibrium between out:out and in:out conformation can be tuned through the interaction with Lewis acids …”
Section: Introductionmentioning
confidence: 99%
“…Phosphatrane molecules are a tricyclic cage‐like heterocycles which present the possibility to have a transannular dative bond with a nitrogen or another heteroatom. The pioneer synthetic work in the groups of Alder and Verkade showed that depending of the size, substituents and environment they can adopt out:out and/or in:out conformations. In previous works, we have demonstrated that the change of the conformation can have profound implications in the nucleophilic character of the terminal phosphorous atom, and thus, the equilibrium between out:out and in:out conformation can be tuned through the interaction with Lewis acids …”
Section: Introductionmentioning
confidence: 99%
“…We have been engaged for some time in studying the chemistry of bridgehead medium-ring diphosphines and their derivatives, 3 partly for comparison with their diamine counterparts which we studied earlier. 4,5 We have reported the preparation of 1,5-diphosphabicyclo [3.3.3]undecane 1, 6 1,6diphosphabicyclo [4.3.3]dodecane 2, 7 and 1,6-diphosphabicyclo-[4.4.3]tridecane 3, 3 but found that although the protonated ion of 1,6-diphosphabicyclo [4.4.4]tetradecane 4 could be made, all attempts at deprotonation lead to deep-seated rearrangements, probably initiated by deprotonation at α-carbon (see later). 3 This suggested that these diphosphines were extremely strong bases, even though they do not possess any conventional means † Atranes are 1,5-diheteroatom derivatives of bicyclo [3.3.3]undecane with some type of bonding interaction between the two bridgehead atoms; proazaphosphatranes are derivatives of 2,5,8,9-tetraaza-1phosphabicyclo [3.3.3]undecane.…”
Section: Introductionmentioning
confidence: 99%
“…Incidentally, it is worth mentioning that a compound of type 12 with halogen atoms other than iodine was spectroscopically detected after treating 11 with halogenating reactants other than diatomics, e.g., C 2 Cl 6 18 or the Grignard species. 18,52 Due to the lack of an X-ray structure, we did not perform any computational analysis.…”
Section: Cracking In Step V Of the Open Chain 10mentioning
confidence: 99%